Impacto de estrategias educativas para mejorar los CAPS (Conocimientos, Actitudes y Practicas) de padres/cuidadores en niños de 5 a 10 años en la población de Guamal – meta 2020 (2021)
Oral hygiene of children must be carried out and accompanied especially by their parents or caregivers until the child is autonomous (8 to 10 years). (Palma & Cahuana, 2010). Objective: To measure the impact of educational strategies to improve the CAPs (Knowledge, Attitudes and Practices)of parents on the oral care of their children aged 5 to 10 years in the GuamalMeta-2020 population. Materials and methods: This study is quasi-experimental pre-post. Inclusion and exclusion criteria were applied for parents / caregivers of children between 5-10 years old. An educational strategy based on a self-authored video was applied to measure the CAPs to obtain 95% confidence and 7.7% error where the informed consent of the parents was obtained. Results: of the present study, the first section contains the sociodemographic variables of the study, the second shows the levels of knowledge, attitudes and practices before and after the educational strategy, in the third section the hypothesis tests carried out to identify whether The educational strategy had a significant impact on the CAPs of parents / caregivers of children aged 5 to 10 years in the municipality of Guamal, Meta. Conclusions: The impact of the educational strategy implemented was significant, because after evaluating the hypothesis tests, it is evidenced that the average grades obtained by parents / caregivers of children aged 5 to 10 years in the Guamal-Meta-2020 population improved significantly afterwards. of applied the pedagogical strategy